Small fiber neuropathy associated with SARS‐CoV‐2 infection. Issue 4 (22nd November 2021) - Abrams, Rory M. C.; Simpson, David M.; Navis, Allison; Jette, Nathalie; Zhou, Lan; Shin, Susan C.
Abstract: Introduction/Aims: The development and persistence of neurological symptoms following severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection is referred to as "long‐haul" syndrome. We aimed to determine whether small fiber neuropathy (SFN) was associated with SARS‐CoV‐2 infection. Methods: We retrospectively studied the clinical features and outcomes of patients who were referred to us between May 2020 and May 2021 for painful paresthesia and numbness that developed during or after SARS‐CoV‐2 infection and who had nerve conduction studies showing no evidence of a large fiber polyneuropathy. Results: We identified 13 patients, Eight women and five men with age ranging from 38–67 y. Follow‐up duration ranged from 8 to 12 mo. All patients developed new‐onset paresthesias within 2 mo following SARS‐CoV‐2 infection, with an acute onset in seven and co‐existing autonomic symptoms in seven. Three patients had pre‐existing but controlled neuropathy risk factors. Skin biopsy confirmed SFN in six, all of whom showed both neuropathy symptoms and signs, and two also showed autonomic dysfunction by autonomic function testing (AFT). Of the remaining seven patients who had normal skin biopsies, six showed no clinical neuropathy signs and one exhibited signs and had abnormal AFT. Two patients with markedly reduced intraepidermal nerve fiber densities and one with normal skin biopsy had severe and moderate coronavirus disease 2019 (COVID‐19); the remainder experienced mild COVID‐19 symptoms. Nine patients received symptomatic neuropathy treatment with paresthesias controlled in seven (77.8%). Discussion: Our findings suggest that symptoms of SFN may develop during or shortly after COVID‐19. SFN may underlie the paresthesias associated with long‐haul post‐COVID‐19 symptoms. Abstract : See Editorial on pages 369‐370 in this issue .